PENGARUH SUBSTITUSI TEPUNG IKAN TERI (STOLEPHORUS COMMERSONII) DAN TEPUNG KACANG MERAH (VIGNA ANGULARIS) TERHADAP DAYA TERIMA DAN KANDUNGAN PROTEIN PIE MINI[The Effect of Anchovy (Stolephorus commersonii) Flour and Red Beans (Vigna angularis) Flour Substitution toward Mini Pie Acceptance and Proteins Content] - Muhammad Nabil Faroj (Universitas Airlangga, 2019)
Anchovy flour and red beans flour are food with high proteins and essential amino acid that could be processed into various foods such as mini pie which could become high-proteins snack. This research aimed to analyze the effect of anchovy flour and red beans flour substitution towards mini pie acceptance and protein content. The design of this formula development study was true experiment with completely randomized design. There were 4 types of treatment (substitution of anchovy flour and red beans flour) with 3 times of replication. There were 25 mothers of children under five involved as untrained panelists. The differences in acceptance level was analyzed by Kruskal Wallis and Mann Whitney test (α ≤ 0.05). The result of organoleptic tests showed the most preferred formula was F3 anchovy flour 62.5 g and red bean flour 15g. The highest increase in proteins content substitution per 100 g mini pie was F3 (9,6 g). There were significant differences between F0 with F1, F2, and F3 for all characteristics (colour p=0.000, aroma p=0.027, texture p=0.002, flavour p = 0.000). The best formula composition was F3 (substituted by anchovy flour 62.5 g and red bean flour 15 g). Mini pie modified by anchovy flour and red bean flour could be functioned as an alternative high protein snack for children under five years old.